The politics of uncertainty : sustaining and subverting electoral authoritarianism - Schedler, Andreas 1964- (Oxford studies in democratization, 2013)
This volume offers a major new theory of authoritarian politics. It studies regime struggles between government and opposition under electoral authoritarianism and argues that autocracies suffer from institutional uncertainties